STRATEGI PENGELOLAAN SHADAQOH CENTELAN AISYIYAH DALAM MENINGKATKAN MINAT MASYARAKAT UNTUK BERSEDEKAH (Studi Kasus: Aisyiyah Ranting Keputih) - Hanik, Umi Atia (Ekosiana Jurnal Ekonomi Syari ah, 2021)
One of the programs carried out by the Muhammadiyah Organization through the Muhammadiyah Covid-19 Command Center (MCCC) is the Muhammadiyah Family Food Security Movement (Getapak). One of the activities at Getapak is Shadaqah Centelan. From this activity, the researcher will examine the Management Strategy of Shadaqoh Centelan Aisyiyah in Increasing Public Interest for Alms (Case Study: Aisyiyah Ranting Keputih). The purpose of this study was to determine how the strategies used to attract people to give alms, and the level of success when using these strategies.The research method used in this research is descriptive qualitative research. The data collection technique uses written and in-depth interviews. After all the data is collected, the data is processed and compiled so that we can find out how the strategy is and the development of the strategy.Through this research, the results show that Aisyiyah Ranting Keputih's strategic way to attract the public's interest in giving charity through online social media such as Whatsaap, Instagram, Facebook, and Mass Media such as Klikmu.co. Apart from online media, there are also offline media, such as announcing that there is a new program, namely shadaqah centelan at the time of recitation and the last one is information by word of mouth. Of the many strategies, the number of donors from 8 became 35 people, and the number of shadaqah centelan from 170 packs to 250 packs. This amount is also a donation fund from Getapak Muhammadiyah which is as much as 1,500,000 which is managed to buy staples for the activities of Sadaqah Centelan. Keywords: Sadaqah, Interests, Strategy.